Opportunistic Microorganisms in Patients with Head and Neck Trauma - Gaetti Jardim Júnior, Elerson; Okamoto, Ana Claudia; Melo, Moriel Evangelista; Schweitzer, Christiane Marie (ARCHIVES OF HEALTH INVESTIGATION, 2013)
The use of antimicrobial agents has facilitated the dissemination of multi-resistant microorganisms, compromising dental and medical treatment. The aim of this study was to evaluate the distribution of different opportunistic microbial species in patients who suffered head and neck trauma, under temporary maintenance in nosocomial environment, particularly intensive care units, on the occurrence of such microorganisms in the oral cavity of the patients. It was selected 38 patients subjected to head and neck traumas. After emergency surgical procedures, clinical samples of saliva, sub and supragingival biofilms and mucosal surfaces were collected at two different moments: just after stabilization of the patient and soon after patients’ release from medical units. The presence of opportunistic and superinfecting microorganisms was evaluated by culture on selective and non-selective media, and the presence of the family Enterobacteriaceae, as well as genera Enterococcus, Pseudomonas, and Staphylococcus was assessed by PCR. It was found that the use of antimicrobials, even for short periods of time was sufficient to facilitate colonization by microorganisms of the families Enterobacteriaceae and Pseudomonadaceae, as well as yeasts and enterococci. These results support the concept that medical and dental teams should make a periodically change of antimicrobials used in treatment protocols in hospital for head and neck trauma patients, in order to minimize dissemination of opportunistic or superinfecting microorganisms. Keywords: Antimicrobial Agents; Head and Neck Trauma; Opportunistic Infections; Hospital Units; Polymerase Chain Reaction; Culture Media.